Geography Education after Natural Disasters: The Tsunami Education Project (TEP) in Sri Lanka - Klose, Thorsten; Laskowski, Sandra (Journal of Geography Education, 2008)
After the Tsunami 2004 most of the rehabilitation activities were focused on the reconstruction of private houses, schools and hospitals, but the affected people in Sri Lanka were not only suffering the loss of their houses. The missing of a deeper geography education in Sri Lankan schools lead to the situation that along the coastal areas different rumours were spread about new tsunamis in the near future which caused an enormous fear among local communities that was slowing down the rehabilitation process. The TEP was one capacity building project within the relief activities. Geography workshops increased the basic knowledge about the reasons of earthquakes and tsunamis mainly for teachers along the affected coastal areas. Scientific knowlegde was used to decrease partly superstitious fear about the ocean and to act against frightening rumours. The didactical concept of the geography workshops was concentrated on the learners' personal knowledge and experience. The TEP underlined the importance of didactical concepts in capacity building projects and pointed out the links between geography education and rehabilitation activities after natural disasters. Facing climate change, the importance of awareness projects with a geographical background will increase in the future especially in developing countries. The development of disaster preparedness strategies in these vulnerable countries will become an important topic and needs clear didactical concepts.